Diverse activities in Spermonde Islands cause serious damage of coral reef and seagrass ecosystem. This research is aimed to assess appropriateness and carrying capacity of gavernance of marine fishery tourism in Spermonde Islands. The research was conducted from March to July 2008 in several islands within Spermonde Archipelago i.e. Sapuli, Satando, Saugi, Cambang-Cambang, Salemo, Sakoala, Sabangko, Sagara, Sabutung and Gusung Torajae. The research stations were determined based on result of - Muhammad Kasnir; Achmad Fahrudin; Dietriech G. Bengen; Mennofatria Boer (Forum Pasca Sarjana, 2009)
Diverse activities in Spermonde Islands cause serious damage of coral reef and seagrass ecosystem.  This research is aimed to assess appropriateness and carrying capacity of gavernance of marine fishery tourism in Spermonde Islands.  The research was conducted from March to July 2008 in several islands within Spermonde Archipelago i.e. Sapuli, Satando, Saugi, Cambang-Cambang, Salemo, Sakoala, Sabangko, Sagara, Sabutung and Gusung Torajae.  The research stations were determined based on result of satellite images.  Date collected were water quality, interview data, and secondary data.  Analysis method of ecosystem condition used line intercept transects, environmental characteristics used principal component analysis, relationship between environmental characteristics and ecosystem potency applied correspondence analysis. feasibility analysis was continued with analysis of carrying capacity.  Results of the research showed that condition of live coral and seagrass were categorized as bad to good.  Based on feasibility analysis, it is known that carrying capacity of floating fish cage is 380 units, seaweed culture is 326 units, scuba diving tourism is 41.58 people/day, snorkeling is 17.82 people/day, coastal tourism is 11.754 people/day, and potency of coral fish is 71.21 tones/year   Keywords: potency, carrying capacity, Spermonde Islands